Decadal-scale urban footprints on seagrass blue carbon dynamics in Palk Bay, India: a remote sensing based framework - Ranith, Rajamohanan Pillai; Menon, Nandini N.; Nobi, E. P.; Haris, Farzana; Raj, Roshin P.; Pettersson, Lasse H. (Frontiers in Marine Science, 2025)
IntroductionSeagrass ecosystems are vital for carbon sequestration, shoreline stabilization, habitat provision, and nutrient cycling, thereby playing a key role in climate mitigation and adaptation. Understanding how anthropogenic pressures affect seagrass ecosystems is essential for effective coastal zone management.MethodsBy integrating decadal satellite-based urbanization metrics with in-situ measurements of seagrass biomass and sediment organic carbon at four sites (Pamban, Mandapam North, Devipattinam, Thondi) for the periods 2010 and 2022, we quantified how the urban expansion affected the seagrass biomass and sediment carbon storage potential. Landsat series satellite imagery was analyzed using the Normalized-Difference-Built-up Index (NDBI) to quantify urban expansion. Relationships with seagrass parameters were analyzed through multivariate statistical approaches, including principal component analysis (PCA).ResultsResults indicated a significant increase in built-up area ( 12 Km2) near high-impact sites (Devipattinam, Thondi), versus 4 Km2 increase at low-impact sites (Pamban and Mandapam North). For the built-up areas, this correlates with elevated suspended sediment matter (SSM) (31.2% increase in high urban sites), reductions in seagrass above-ground biomass (AGB: -25.52% of high urban sites), and decreased sediment organic carbon (SOC: -42.67%). Multivariate analyses, also revealed strong associations between urbanization, SSM, biomass loss, and sediment organic carbon reduction.Discussion and conclusionThese findings demonstrate that coastal urbanization in Palk Bay significantly undermines seagrass blue carbon potential and beneficial ecosystem services. The integrated field and remote sensing approach provides a scalable framework for monitoring tropical seagrass ecosystems, offering actionable insights for coastal zone management, conservation, and climate mitigation under increasing anthropogenic pressures.